A computerised system for measurement of the radial displacement of the intervertebral disc using a laser scanning device. Issue 3 (3rd May 2020) - Fewster, Kayla M.; Haider, Shahid; Gooyers, Chad E.; Callaghan, Jack; Wong, Alexander
ABSTRACT: A computerised system for measuring radial displacement of the intervertebral disc (IVD) based on laser scanning was developed and validated. The system is designed to allow for quantitative analysis of changes in peak IVD displacement on the posterior and anterior side of the disc. This computerised system facilitates quantifying the magnitude of IVD bulging across loading conditions and postures to better understand the structural changes that occur in the IVD of functional spinal units. Experimental results show that the proposed system achieves errors of less than 0.2 mm when compared to phantom 3D-printed models resembling biofidelic spinal units with known measurements. The proposed system is currently in operational use as an analysis tool for studying the relationship between peak IVD displacement, posture and load.